Limited Effect of Dopaminergic Medication on Straight Walking and Turning in Early-to-Moderate Parkinson’s Disease during Single and Dual Tasking - Elshehabi, Morad; Maier, Katrin S.; Hasmann, Sandra E.; Nussbaum, Susanne; Herbst, Heinz; Heger, Tanja; Berg, Daniela; Hobert, Markus A.; Maetzler, Walter (Frontiers in Aging Neuroscience, 2016)
Background: In Parkinson’s disease (PD), the effects of dopaminergic medication on straight walking and turning were mainly investigated under single tasking (ST) conditions. However, multitasking situations are considered more daily relevant. Methods: Thirty-nine early to moderate PD patients performed the following standarized ST and dual tasks (DT) as fast as possible for one minute during On- and Off-medication while wearing inertial sensors: straight walking and turning, checking boxes, and subtracting serial 7s. Quantitative gait parameters, as well as velocity of the secondary tasks were analyzed. Results: The following parameters improved significantly in On-medication during ST: gait velocity during straight walking (p=0.03); step duration (p=0.048) and peak velocity (p=0.04) during turning; velocity of checking boxes during ST (p=0.04) and DT (p=0.04). Velocity of checking boxes was the only parameter that also improved during DT. Conclusion: These results suggest that dopaminergic medication does not relevantly influence straight walking and turning in early to moderate PD during DT.